The Poor of the North Rural Area of Transforming Russia: Double Exclusion - Светлана Сергеевна Ярошенко (Journal of Economic Sociology, 2010)
The paper provides the analysis of the mechanism of stagnant poverty formation. The analysis is done on the basis of the longitudinal survey of the official poor and the territorial study of the north rural area. Rural poor are considered as one of the most deprived and socially-excluded groups, which are characterized by economic, social and spatial isolation from the main sources of life support in capitalistic Russia. This isolation is an important factor of the transformation from statistical group of poor to the real one. The main distinction of this group is not the lack of means to live but the stability of this position, recognition of inability to overcomeindigenceand special adaptation to support the family under the conditions of the exclusion from the labour market and inclusion into the system of social protection. However social help aimed at only the support of the achieved living standards could not be the channel for upward mobility for its receivers.